Manish Sabharwal: 'In Five Years, 25% of the World's Workers Will Be Indian' - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2007)
Four years ago, Manish Sabharwal headed India Life, the country's largest business process outsourcing firm in the field of human resources. Having sold India Life to Hewitt Associates in 2002, Sabharwal has now carved out another niche in the HR business as the chairman of TeamLease, a temporary staffing firm headquartered in Bangalore. With more than 450 offices all over India and 67,000 employees, the company has a good shot at becoming the country's largest employer in the private sector by the end of 2007, Sabharwal says. In an interview with India Knowledge@Wharton, he discusses the opportunities and challenges of running "India's largest temping company."